2009
DOI: 10.1098/rspb.2009.0799
|View full text |Cite
|
Sign up to set email alerts
|

Impact of naturally spawning captive-bred Atlantic salmon on wild populations: depressed recruitment and increased risk of climate-mediated extinction

Abstract: The assessment report of the 4th International Panel on Climate Change confirms that global warming is strongly affecting biological systems and that 20–30% of species risk extinction from projected future increases in temperature. It is essential that any measures taken to conserve individual species and their constituent populations against climate-mediated declines are appropriate. The release of captive bred animals to augment wild populations is a widespread management strategy for many species but has pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
110
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 105 publications
(118 citation statements)
references
References 49 publications
1
110
1
Order By: Relevance
“…The level of introgression decreased dramatically after 1996 (Table 3), which may indicate dilution of foreign genes in the wild gene pool consistent with decreased fitness of alleles originating from farmed individuals (e.g. McGinnity et al, 1997McGinnity et al, , 2009Martinez et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The level of introgression decreased dramatically after 1996 (Table 3), which may indicate dilution of foreign genes in the wild gene pool consistent with decreased fitness of alleles originating from farmed individuals (e.g. McGinnity et al, 1997McGinnity et al, , 2009Martinez et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…In Atlantic salmon, hatchery releases may threaten genetic integrity of even geographically distant wild salmon populations (Vasemägi et al, 2005). The escape or deliberate introduction of captive bred animals into the wild can substantially depress natural recruitment and more specifically can disrupt the capacity of natural populations to adapt to higher winter water temperatures associated with climate variability (McGinnity et al, 2009). In addition, our results suggest that in the present conditions of accelerated climate warming the risk is even higher, because warm conditions will likely enhance mobility of hatchery individuals among rivers in a region.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A 37-year study of Atlantic salmon in Ireland [57] found that naturally spawning farmed fish depress wild recruitment and disrupt the capacity of natural populations to adapt to higher water temperatures associated with climate change. Hansen et al [58] examined Danish populations of brown trout subject to hatchery supplementation for 60 years and found evidence for selection in the wild against alleles associated with non-native hatchery fish.…”
Section: Among Populationsmentioning
confidence: 99%